Rare bird documentation form for Greater Scaup at Little Clear Lake in 1985 - Jardine, Wallace E.et al (1985)
Rare bird documentation form for twenty-five to thirty Greater Scaups at Little Clear Lake in Pocahontas County, IA on April 7, 1985. Epson - sheet feed